2014
DOI: 10.1039/c3ra43512a
|View full text |Cite
|
Sign up to set email alerts
|

Fuels and plastics from lignocellulosic biomass via the furan pathway; a technical analysis

Abstract: Biorefineries convert biomass into bio-based products, which have the potential to replace typical products produced by petroleum refineries. They provide a technology platform to reduce anthropogenic greenhouse gas emissions, increase security of supply and reduce the dependency on crude oil. The biorefinery concept presented in this paper focuses on a combination of (1) organosolv fractionation to produce carbohydrates from lignocellulosic biomass and (2) the furan technology to convert carbohydrates into po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
94
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(95 citation statements)
references
References 39 publications
1
94
0
Order By: Relevance
“…The elemental mappings showed fairly homogeneous metal dispersions; no particles of bulk zirconia or alumina were observed, which is consistent with the PXRD studies. The EDS analyses of (Zr) SSIE -beta and (ZrAl) SSIE -beta indicated that they possess similar atomic ratio Si/(Zr+Al) (16)(17)(18)(19) (Table 2), which is consistent with the fact that the molar amounts of Zr or (Zr+Al) added to deAl-beta were the same for the two materials ( Table 1). The atomic ratio Al/Zr was higher for (ZrAl) SSIE -beta than (Zr) SSIE -beta (1.2 and 0.03, respectively), and the Si/Al ratio was much lower for (ZrAl) SSIE -beta (35 compared to 588 (Zr) SSIE -beta), which is consistent with the fact that (ZrAl) SSIE -beta was obtained via SSIE for both Zr and Al.…”
Section: Beta Type Materialssupporting
confidence: 81%
See 2 more Smart Citations
“…The elemental mappings showed fairly homogeneous metal dispersions; no particles of bulk zirconia or alumina were observed, which is consistent with the PXRD studies. The EDS analyses of (Zr) SSIE -beta and (ZrAl) SSIE -beta indicated that they possess similar atomic ratio Si/(Zr+Al) (16)(17)(18)(19) (Table 2), which is consistent with the fact that the molar amounts of Zr or (Zr+Al) added to deAl-beta were the same for the two materials ( Table 1). The atomic ratio Al/Zr was higher for (ZrAl) SSIE -beta than (Zr) SSIE -beta (1.2 and 0.03, respectively), and the Si/Al ratio was much lower for (ZrAl) SSIE -beta (35 compared to 588 (Zr) SSIE -beta), which is consistent with the fact that (ZrAl) SSIE -beta was obtained via SSIE for both Zr and Al.…”
Section: Beta Type Materialssupporting
confidence: 81%
“…Besides FA, various useful bio-products, such as alkyl furfuryl ethers (FEs), levulinate esters (LEs), angelica lactones (AnLs), levulinic acid (LA), and -valerolactone (GVL) can be produced from Fur (Scheme 1) [13][14][15]. For example, FEs are used as blending components of gasoline [16,17] and as flavours [18,19]. LEs are useful chemical intermediates for producing coatings, resins and flavour preparations [20,21], anticancer agents, pesticides and insecticides [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Successful commercialization of lignocellulosic bioreneries requires development of costeffective pretreatment technologies to overcome the resistance of lignocellulose materials against chemical and microbial attack. 4 A preferential pretreatment process should aim at maximizing the yield of products while minimizing the environmental impact from the generated emissions and waste streams.…”
Section: Introductionmentioning
confidence: 99%
“…It can be converted to the bio-products furfuryl alcohol (FA), furfuryl alkyl ethers (FEs), levulinate esters (LEs), levulinic acid (LA), angelica lactone isomers (AnLs) and -valerolactone (GVL) [2][3][4] (Scheme 1), useful in different sectors of the chemical industry. FA, industrially produced via hydrogenation of Fur, is used in the foundry 3 industry [5], and FEs are used as blending components of gasoline [6,7] and as flavour compounds [8,9]. LEs are used as oxygenate fuel additives [10][11][12], solvents, and to produce plasticizers and flavouring agents [13][14].…”
Section: Introductionmentioning
confidence: 99%